2021
DOI: 10.3390/ijerph182010827
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Mental Health, Educational Burnout and Strategies for Coping with Stress among Students: A Cross-Sectional Study of Poland

Abstract: This study sought to investigate the risk factors of poor psychosomatic health among students during the quarantine of the first wave of the COVID-19 pandemic. A survey was conducted on-line, on a sample of 1978 respondents in Poland. The study was carried out towards the end of the summer 2020 semester. The questionnaire used in the study was designed so that it allows for the observation of the main risk factors which have an impact on the students’ mental health. Variance analysis and hierarchical regressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Existing literature corelates educational burnout with emotional exhaustion. Educational challenges during COVID-19 lockdown are generally defined as perceived stress and pressure to face the tasks and student duties [10,11] mostly in an online environment, coupled with an increased workload.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature corelates educational burnout with emotional exhaustion. Educational challenges during COVID-19 lockdown are generally defined as perceived stress and pressure to face the tasks and student duties [10,11] mostly in an online environment, coupled with an increased workload.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies [1,3,4,10,20], medical students suffer significant levels of stress throughout college, which is linked to the state of burnout. The Dyrbye study [21] conducted in seven American colleges revealed that 52.8% of medical students had burnout, which was associated with self-reported unprofessional conduct and less altruistic professional values.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout can also occur in educational environments, particularly during such events as the first wave of the COVID-19 pandemic, for instance [ 22 ], when “an increase in the level of educational burnout, a decrease in life satisfaction, and the use of negative strategies of coping with stress were accompanied by a deteriorated mental condition of students, with female respondents scoring higher on the scale of disorders in comparison to males”.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, student burnout is positively related to mental health problems, including depression, anxiety ( 41 ), and psychopathological symptomatology ( 74 ). A COVID-19- related study on the correlation of emotional exhaustion with mental health revealed that, around the outbreak of COVID-19, the mental health of college students decreased with the increase of student burnout, especially emotional exhaustion ( 37 , 75 ). A similar finding reported that student burnout is positively correlated with depression among medical students ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that emotional exhaustion is a negative indicator of mental health ( 37 , 38 ). Greater emotional exhaustion is associated with poorer mental health ( 39 ).…”
Section: Literature Reviewmentioning
confidence: 99%